Presence of Dirofilaria immitis (Leidy, 1856) in dogs from a shelter in the Sucre Canton, Ecuador - López-Rauschenberg, María Karolina (2023)
Dirofilariasis is a zoonotic disease with worldwide distribution transmitted by Aedes, Anopheles and Culex mosquitoes to animals and humans. The objective of the study was to evaluate the prevalence of the heartworm Dirofilaria immitis (Leidy, 1856) in the shelter "El perro feliz" in the Sucre canton, Ecuador during the year 2021 diagnosed by the thick drop method. A descriptive study was carried out, and a sampling of 100 apparently healthy dogs was carried out during the months of September and October 2020. The thick drop method with Wright staining was used for the microscopic observation of the parasite morphology. The data obtained were analyzed through the percentage method to determine the percentage of positive animals and the ꭓ2 test (Chi-square) of independence at 5% significance to identify the relationship between the variables (age, sex, genetic group, color coat and weight). Thirty-six positive animals were found, representing a 36% prevalence of D. immitis in the study area. It was verified that the behavior of the parasite does not bear any type of relationship with the variables under study; and it is concluded that the disease can be transmitted to dogs without distinction of sex, age, genetic group, coat color and weight. This study describes, for the first time, seropositivity to D. immitis in a canine population of the Sucre canton, which represents a potential threat to public health; therefore, more studies are needed to determine the incidence of the disease in hosts and its impact on humans.